Operationalization of footballers` emotional intelligence in the dimensions of motivational orientation: analysis based on the basic positions - Popovych, I.; Plokhikh, V.; Hrys, A.; Pavliuk, M.; Nosov, P.; Zinchenko, S. (Journal of Physical Education and Sport, 2023)
The purpose is to conduct empirical research on the correlation of emotional intelligence with footballers` motivational orientation by functional realization (the basic position). The study identifies differences in the parameters of footballers` emotional intelligence by the basic position. The research involved 74 footballers representing such football clubs: FC "Krystal" (Kherson, Ukraine), FC "Chliba Khersonshchyny" (Kherson, Ukraine), FC "Enerhiia" (Nova Kakhovka, Ukraine), FC "Mykolaiv" (Mykolaiv, Ukraine). Research methods: valid and reliable psycho-diagnostic instruments - the method "EQ questionnaire" (Hall, 2000) and questionnaire "Athlete`s Motivational Orientation" ("AMO") (Smoldovskaya, 2022); purposeful non-participant observation with standard protocols; statistical methods for identifying significant differences. Results. The study established empirically and substantiated that functional realization (the basic position) in footballers` competition activities correlates with motivational orientation and sufficiently developed emotional intelligence. The integral index of emotional intelligence (IIEQ) of strikers (Me=38.0) and midfielders (Me=38.0) is characterized by a high level and obvious motivational orientation towards a high result. The study shows that a high level of development of footballers` ability to manage their emotions and self-motivation corresponds to a high level of involvement in the activity performed and aspiration for team cohesion, for a synergetic contact with spectators. Four strongest (?<.010) significant correlations of self-motivation with subject-directed (rs=.289), result-directed (rs=.344) and personally-directed motivational orientation (rs=.244) and empathy with socially-directed motivational orientation (rs=.267) were established. Conclusions. The study substantiates that focusing on the development of footballers` emotional intelligence, in particular, of such parameters as self motivation and empathy can give an essential advantage over competitors. It shows that the obtained scientific facts constitute a number of operational elements which should be taken into consideration by coaches in team sports.